Plan de negocios para la creación de una fábrica de productos derivados de la soya, cantón Quevedo, año 2015. - Núñez Albiño, Silvia Patricia (2016)
The business plan is a management tool within the current trends for the preparation of investment projects. The study's main objective was to make a business plan for the creation of a factory of products derived from soy milk, tofu (cheese) and soy meat in Canton Quevedo, 2015. It is divided in phases, which are market research, technical study, social impact - environmental and ends with the economic study - financial, wherein the evaluation and feasibility of the project is done. The market study was to identify the population or consumer products derived from soybeans segment, where it was determined that much compared to the population consumed products derived from soybeans and that there is a market segment that requires acquiring products of this type, including soy products most in demand are: milk, tofu (cheese) and meat. The technical study determined the location of the factory according to various factors such as acquisition of raw material, type of machinery, equipment and tools required for the different manufacturing processes of the products was chosen to Km 3 road to El Empalme, to have closeness and proximity to the consumer market and the most suitable organizzacional structure which is made by the general manager, a secretary, a production supervisor and three workers it was also determined. This study determines the trade name of the company, which is ALISOYA S.A., soy foods S.A. taking as a marketing strategy two ways: shops, supermarkets wholesalers and of course the final consumer directly. The environmental impact determines that the project does not exert greater impact because chelates technology used is artisanal. Finally the economic study - financial determined that the business plan for factory products derived from soybeans obtained a $ 239.792,02 NPV, IRR 97,65% and a cost / benefit ratio of $ 1.18, Breakeven $ 40.411,06, PRI es de 1 year, 3 months y 3 days results prove the feasibility, viability and profitability of the proposed project.